2020
DOI: 10.1001/jamacardio.2020.3638
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Care and Outcomes Among Medicare Advantage vs Fee-for-Service Medicare Patients Hospitalized With Heart Failure

Abstract: MA), a private insurance plan option, now covers one-third of all Medicare beneficiaries. Although patients with cardiovascular disease enrolled in MA have been reported to receive higher quality of care in the ambulatory setting than patients enrolled in fee-for-service (FFS) Medicare, it is unclear whether MA is associated with higher quality in patients hospitalized with heart failure, or alternatively, if incentives to reduce utilization under MA plans may be associated with worse care. OBJECTIVE To determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…In a study of 262 626 patients hospitalized with HF included in GWTG-HF, inclusion in the Medicare Advantage program was compared with inclusion in the fee-for-service Medicare. 34 Patients included in the Medicare Advantage program were more likely to be discharged home (adjusted OR, 1.16 [95% CI, 1.13–1.19]; P <0.001) despite lower odds of discharge within 4 days (adjusted OR, 0.97 [95% CI, 0.93–1.00]; P =0.04). In addition, no difference was reported in in-hospital mortality.…”
Section: Quality Of Carementioning
confidence: 99%
“…In a study of 262 626 patients hospitalized with HF included in GWTG-HF, inclusion in the Medicare Advantage program was compared with inclusion in the fee-for-service Medicare. 34 Patients included in the Medicare Advantage program were more likely to be discharged home (adjusted OR, 1.16 [95% CI, 1.13–1.19]; P <0.001) despite lower odds of discharge within 4 days (adjusted OR, 0.97 [95% CI, 0.93–1.00]; P =0.04). In addition, no difference was reported in in-hospital mortality.…”
Section: Quality Of Carementioning
confidence: 99%
“…Figueroa and colleagues correctly point out that MA plans practice utilization management to help guide hospital discharge disposition, which may promote more appropriate home discharges and lower postacute costs, while also noting MA plans leverage additional care coordination services to support patients. Considering that the Centers for Medicare & Medicaid Services continues to regulate quality performance of both MA plans and hospitals, including all-cause readmissions, MA plans should continue partnering with hospitals and clinicians to support evidence-based inpatient management while studying and aligning benefit design for optimal patient outcomes along the continuum of care.…”
mentioning
confidence: 78%
“…To the Editor Figueroa and colleagues reported that fee-for-service (FFS) Medicare and Medicare Advantage (MA) inpatients with heart failure shared similar complexity, clinical interventions, and outcomes but raised concerns that more MA inpatients were discharged home (adjusted odds ratio, 1.16; 95% CI, 1.13-1.19; P < .001) compared with a skilled nursing facility (SNF) as a quality difference driven mainly by MA plan cost interest. I would suggest clinically appropriate hospital-to-home discharge is a potential quality indicator aligned with Medicare patient interest.…”
mentioning
confidence: 99%
“…Currently, only a minimal proportion of elderly patients hospitalized for HF participate in CR. 18,19 A scientific statement from the American Heart Association emphasized the importance of prioritizing functional capacity as a principal end-point for therapies oriented to older adults with cardiovascular disease. 38 However, there is a dearth of research specifically addressing the diverse population of older patients hospitalized for HF.…”
Section: Discussionmentioning
confidence: 99%